Antiphospholipid Antibodies in Healthy Serbian Middle-Aged Subjects: Preliminary Data - Becarevic, Mirjana; Jovičić, Snežana; Ignjatović, Svetlana; Mirković, Duško (Journal of Medical Biochemistry, 2022)
Backgroud: The investigation of the prevalence of the IgG and the IgM isotypes of anticardiolipin (aCL) and anti-β2glycoprotein I (aβ2gpI) Abs in healthy Serbian middle-aged subjects was the main goal of our study. In addition, we analyzed the potential associations of above-mentioned Abs with serum proteins and lipids/lipoproteins. Methods: Forty healthy subjects were included in our study. Obesity (BMI ≥ 30 kg/m2) was present in 8/40 (20%) subjects. Titers of analyzed Abs were measured by ELISA. Results: The prevalence of IgG and IgM aβ2gpI Abs was 5% and 12.5%, respectively, while the prevalence of IgM aCL was 10%. The IgG aβ2gpI Abs were significantly different between subjects with normal triglycerides levels and those with hypertriglyceridemia (Mann-Whitney, P = 0.014). The significant difference in hsCRP concentrations was observed between subjects with the increased levels of the IgM isotype of aCL Abs and those with normal IgM aCL values (Mann-Whitney, P = 0.028). Conclusion: Dyslipidemia and BMI ≥30 were associated with aPL Abs and therefore, the correction of BMI and lipid status might be beneficial in reduction or elimination of predisposing factors that might trigger thrombotic events in otherwise healthy middle-aged subjects. Larger national study is necessary to confirm our findings.